2011
DOI: 10.1097/mao.0b013e3182204526
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Minimizing Trauma During Conventional Cochlear Implantation

Abstract: Objective To describe the relationship between implantation-associated trauma and postoperative speech perception scores among adult and pediatric patients undergoing cochlear implantation using conventional length electrodes and minimally traumatic surgical techniques. Study Design Retrospective chart review (2002–2010). Setting Tertiary academic referral center. Patients All subjects with significant preoperative low-frequency hearing (≤70 dB HL at 250 Hz) who underwent cochlear implantation with a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
181
5
11

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(202 citation statements)
references
References 30 publications
5
181
5
11
Order By: Relevance
“…While Carlson et al (7), reported significantly better word perception scores in CI recipients with preserved residual hearing, Balkany et al (8), D'Elia et al (9), and Cosetti et al (10) could not demonstrate such an effect.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…While Carlson et al (7), reported significantly better word perception scores in CI recipients with preserved residual hearing, Balkany et al (8), D'Elia et al (9), and Cosetti et al (10) could not demonstrate such an effect.…”
mentioning
confidence: 87%
“…The assessment of residual acoustic hearing close to the maximum output of the audiometer leads to a ceiling effect causing an underestimation of the postoperative hearing loss and an overestimation of hearing preservation rates. To take this effect into account, different hearing preservation classifications have been proposed (7)(8)(9)(10)15). The advantage of the HEARRING group hearing preservation classification system (11) is that the postoperative PTA is related to the preoperative PTA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, limiting injury potentially allows for the application of future technologies, such as cellular regeneration or other novel cochlear nerve stimulation technologies (Carlson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Intracochlear trauma should be minimized during modern-day cochlear implantation surgeries (1). It has been shown that better performance of cochlear implant recipients with minimal residual hearing is correlated with minimizing cochlear trauma (2Y4).…”
mentioning
confidence: 99%